Evaluation of Potential Complications of Interstitial Lung Disease Associated With Antiandrogens Using Data From Databases Reporting Spontaneous Adverse Effects - Nawa, Hideki; Niimura, Takahiro; Hamano, Hirofumi; Yagi, Kenta; Goda, Mitsuhiro; Zamami, Yoshito; Ishizawa, Keisuke (Frontiers in Pharmacology, 2021)
From 2002 to 2018, the number of patients with prostate cancer significantly increased from 679,023 to 1276,106 worldwide. Total prostatectomy (including robot-assisted prostatectomy), radiation therapy, and pharmacological treatment are commonly used to treat prostate cancer. The Chief of the Pharmaceutical Safety Division, that is, the Federation of Pharmaceutical Manufacturers’ Associations of Japan (FPMAJ), recently called for the revision of package inserts for ethical drugs. However, the pathogenesis of interstitial lung disease (ILD), a serious drug-induced adverse effect, remains unclear. Moreover, there have been no large-scale evaluations of potential complications associated with currently used antiandrogens, which are commonly employed to treat prostate cancer. Hence, ILD, as an adverse event, remains poorly understood. Therefore, we conducted a survey of reports in the Japanese Adverse Drug Event Report (JADER) database to investigate the potential association between the reporting of ILD and antiandrogen drug use in clinical practice. The occurrence of ILD was investigated by evaluating the relationship between antiandrogen drug use and ILD. Adverse event signals were detected with reporting odds ratios (RORs), using data from the JADER and FDA Adverse Event Reporting System (FAERS) databases, for the analysis of post-marketing adverse event reports. The JADER was used to examine the time profile of adverse event occurrence for each drug, whereas the FAERS was used to screen cases of unknown adverse events and analyze their trends of occurrence. The analysis of data from both databases revealed the 95% confidence interval lower limits of ROR for bicalutamide and flutamide to be >1, and adverse event signals were detected following the use of either drug. While caution should be exercised for drugs that are new to the market, we conclude that drugs with similar therapeutic effects that have been in use for a long period should also be re-examined for potential adverse events.